Effects of Chinese herbal medicine Xiangbin prescription on gastrointestinal motility - Jiang, Zhi; Cao, Li-Xing; Liu, Bo; Chen, Qi-Cheng; Shang, Wen-Fan; Zhou, Lu; Li, Dan-Yan; Guo, De-An; Chen, Zhi-Qiang (World journal of gastroenterology : WJG, 2017)
To investigate the effects of Xiangbin prescription (XBP), a Chinese herbal concoction, on gastrointestinal motility. Forty healthy volunteers were recruited for this randomized controlled trial of XBP. Antroduodenojejunal manometry was used to monitor gastrointestinal motility in these subjects. After the subjects had fasted for at least 12 h, XBP ( = 30) or placebo ( = 10) was orally administrated and gastrointestinal motility was recorded for 4 h. Plasma motilin and ghrelin were measured by enzyme-linked immunosorbent assay. Oral administration of XBP significantly increased the amplitude of duodenal contractions [19.5 (13.0-26.7) 16.9 (12.3-23.9), < 0.05], jejunal contractions [18.3 (15.3-25.0) 15.4 (11.7-23.9), < 0.01], and the motility index of duodenal contractions [522.0 (146.0-139.0) 281.0 (76.5-1006.0), < 0.01] in phase II of the migratory motor complex (MMC), which subsequently initiated the MMC cycle [74.0 (30.0-118.0) 116.5 (24.0-219.0), < 0.05], shortened the duration of phase I of the MMC [42.0 (0.0-90.0) 111.5 (42.0-171.0), < 0.01], and lengthened the duration of phase II of the MMC [120 (21-240) 58 (16-170), < 0.01] compared to the duration before XBP administration. There were significant differences in the amplitude of jejunal contractions [19.8 (14.0-30.0) 18.0 (13.0-28.5), < 0.05], the motility index of duodenal contractions [236.0 (115.0-306.0) 195.0 (109.0-310.0), < 0.05)], and jejunal contractions [214.0 (95.0-403.0) 178.0 (55.0-304.0), < 0.01] in phase III of the MMC. Oral administration of XBP greatly increased plasma motilin (57.69 ± 9.03 49.38 ± 8.63, < 0.01) and ghrelin (279.20 ± 104.31 238.73 ± 115.59, < 0.01) concentrations compared to concentrations after oral administration of the placebo. XBP can stimulate duodenal and jejunal motility and increase the concentrations of plasma motilin and ghrelin. The clinical applicability of XBP in treating GDIM deserves investigation.